2008
DOI: 10.1002/app.28780
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, structural elucidation, molecular weight determination, and molecular recognition of first‐ and second‐tier dendrimer molecules

Abstract: 1,3,5-Triglyceratetriazine [first tier (G 1 )] and tri(1,3,5-triglycerate) triazine [second tier (G 2 )] dendrimers were prepared with 1,3,5-trichlorotriazine and sodium glycerate in a 1 : 3 mass ratio in an ethanolic medium. G 1 and G 2 were amorphous, white, solid substances. Their structures were elucidated with IR, 1 H-NMR, and 13 C-NMR, and their thermal stability was studied with thermogravimetric analysis. The activation energy was calculated with the Freeman-Carroll model. Densities, viscosities, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The melamine ring in the resin macromolecule occupied a centermost location referred to as a core22. An expression of the C atom of the melamine ring at core is totally shattered as the ring is embedded in the deepest zone with respect to the growth of the resin with N(CH 2 O) 2 C pyrrolidone ring which acts as dendrimer units23. The O atom of the N(CH 2 O) 2 Cpyrrolidone ring also influenced the C electron density.…”
Section: Resultsmentioning
confidence: 99%
“…The melamine ring in the resin macromolecule occupied a centermost location referred to as a core22. An expression of the C atom of the melamine ring at core is totally shattered as the ring is embedded in the deepest zone with respect to the growth of the resin with N(CH 2 O) 2 C pyrrolidone ring which acts as dendrimer units23. The O atom of the N(CH 2 O) 2 Cpyrrolidone ring also influenced the C electron density.…”
Section: Resultsmentioning
confidence: 99%
“…The melamine ring in the resin macromolecule occupied a centermost location referred to as a core 22 . An expression of the C atom of the melamine ring at core is totally shattered as the ring is embedded in the deepest zone with respect to the growth of the resin with NA(CH 2 AO) 2 ACA pyrrolidone ring which acts as dendrimer units 23 . The O atom of the ANA(CH 2 AO) 2 CApyrrolidone ring also influenced the C electron density.…”
Section: Melamine Ring In Resin Moleculementioning
confidence: 99%
“…Therefore, the dendrimers as vehicles must not react or damage drug structures during the binding and carrying processes. Singh et al 6,11 reported 2,4,6-tridiethyl malonate triazine (TDEMTA), 2,4,6-hexadiethyl malonate triazine (HDEMTA), 1,3,5-triglyceratetriazine, and tri(1,3,5-triglycerate) triazine dendrimers with certain safer binding molecules, such as poly(vinyl pyrrolidone), glycerol, and sodium diethyl malonate esters (SDEME). With this pattern, TTDMM and TTDEM have been characterized and used to bind SB and release.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Thus, a critical transition for supramolecular structures is seen as a new trend for the development of multiapplications of a single molecule. 5,6 In general, their synthesis has been made either through convergent or divergent approaches. [7][8][9] For a long time, composites of several molecular species with required physicochemical properties have been prepared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation